2023
DOI: 10.1007/s40519-023-01532-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between night eating syndrome and health-related quality of life in Korean adults: a nationwide study

Abstract: Purpose Quality of life may be influenced by the presence of eating disorders. This study investigated the association between night eating syndrome (NES) and health-related quality of life in the general population. Methods Data were from the 2019 Korea Community Health Survey. The presence of NES was determined using the Night Eating Questionnaire. Health-related quality of life was measured using the 3-level EuroQoL-5 Dimension Index. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Upon reviewing the abstracts of articles obtained through a search on Medline (OVID) and SCOPUS, five additional relevant articles were included. After the screening process, 30 studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] assessing NES met the inclusion criteria and were thus included in this scoping review. The need for further research into NES within adult populations is reiterated through the limited number of relevant studies yielded through this search.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Upon reviewing the abstracts of articles obtained through a search on Medline (OVID) and SCOPUS, five additional relevant articles were included. After the screening process, 30 studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] assessing NES met the inclusion criteria and were thus included in this scoping review. The need for further research into NES within adult populations is reiterated through the limited number of relevant studies yielded through this search.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1 , only five studies investigated NES in a representative participant sample [ 26 , 27 , 32 , 37 , 44 ], whilst fourteen studies reported on university students [ 17 , 19 , 24 , 25 , 33 , 34 , 35 , 39 , 40 , 41 , 42 , 43 , 45 , 46 ] and ten studies reported on patients within outpatient clinics [ 18 , 20 , 21 , 22 , 23 , 28 , 29 , 30 , 36 , 38 ]. Most studies [ 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 32 , 34 , 36 , 37 , 39 , 42 , 43 , 44 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations